THE INCA GARCilASO BEI'WEEEN THE ANCIENT AND THEMODERN - Chang Rodriguez, Raquel (2009)
Relación de la descendencia del famoso Garci Pérez de Vargas is the shortest work of the IncaGarcilaso and the least attended by the critique. Finished in 1596 and published in1929 in Madrid and Lima, and later studied by Raúl Porras Barrenechea ( 1951), it was conceived as part of the prologue of The Florida of the Inca (1605), dedicated to Teodosioof Portugal, duke of Braganza (1568-1630). My presentation will deal with the portionof the Relation where the author, referring to central figures- Garci Sanchez of Badajoz(1460-1526), Cristóbal de Castillejo (1490-1550) and Garcilaso de la Vega (1501-1536)-,comes in the polemic on tradition and innovation in the Spanish poetry. By relying onthese names, the author of the Commentarios proves to be an attentive reader of poetry,up to date on the literary debate of the epoch and conscious of the beauty of the metricsand traditional tapies, as well as attracted by the "dolce stil novo" supported by hishomonym, Garcilaso of the Vega, the toledano.